Students' perspectives regarding clinical preceptors (CPs) in the baccalaureate undergraduate nursing programme in Karachi, Pakistan - Amina Aijaz Khowaja; Jacqueline Maria Dias (University of Johannesburg, 2019)
Introduction Clinical practice is considered an integral part of nursing education. It is in the clinical area that the students integrate the theory learnt in the classroom into practice. An enabling clinical environment with the assistance of a clinical preceptor (CP) ensures that student nurses become independent practitioners and competent in their roles and responsibilities. Design A comprehensive study was undertaken to explore the emerging role of CPs in Pakistan. This research has been reported in the literature. This paper will deal exclusively with the perceptions of nursing students when working with CPs in the four-year undergraduate baccalaureate program at a private school of nursing (SON) in Pakistan. Through focus group discussions, the perceptions of undergraduate students were explored. Results Four main themes emerged. These included the creation of a conducive clinical environment, development of competencies, engagement in patient care, and personal and professional development. Conclusion Based on the study findings, recommendations for strengthening the role of CPs in supporting undergraduate nursing students in their clinical practice are presented. How to cite this article: KHOWAJA, Amina Aijaz; DIAS, Jacqueline Maria. Students' perspectives regarding clinical preceptors (CPs) in the baccalaureate undergraduate nursing programme in Karachi, Pakistan. Scholarship of Teaching and Learning in the South. v. 3, n. 1, p. 26-35, Apr. 2019. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=68&path%5B%5D=39 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/